Green Accounting, Carbon Emission Disclosure, Sustainable Development: The Moderating Role of Environmental Management System - Asyadiah, Nessa; Huda, Syamsul; Nurhanifah, Afifa (Universitas Gorontalo, 2025)
This study examines the effect of Green Accounting and Carbon Emission Disclosure on Sustainable Development, with the Environmental Management System as a moderating variable, in infrastructure sector companies listed on the Indonesia Stock Exchange. The study uses secondary data and is analyzed using multiple linear regression. The results show that Green Accounting and Carbon Emission Disclosure have a positive effect on Sustainable Development. However, the Environmental Management System does not moderate the relationship between Green Accounting and Sustainable Development, nor between Carbon Emission Disclosure and Sustainable Development.